2023
DOI: 10.1177/21582440231155063
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of the Teachers on Challenges and Possibilities to Online System of Education amid COVID-19 Outbreak in Balochistan, Pakistan

Abstract: The study investigates the issues of access, quality, and other major challenges to the online system of education for students in Balochistan during this pandemic of Covid-19. Using the mixed-method design, 100 participants from schools and 7 curriculum experts responded to the survey and the interview questions. Survey results suggested that majority of the schools have enough digital devices, and teachers, to some extent, have skills to use technology in teaching, but limited electricity, funds, weak intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Furthermore, several studies (Aguirre-Mendez & Mahoney, 2020; Gul et al, 2023; Huda et al, 2018) indicate that students who participate in online learning that focuses on cultural exchange undergo intellectual transformation. In a study (Ahmad & Gul, 2021), participants reported developing a stronger sense of civic leadership and social justice beliefs through online engagements.…”
Section: The Benefits Of Online Discussion Forumsmentioning
confidence: 99%
“…Furthermore, several studies (Aguirre-Mendez & Mahoney, 2020; Gul et al, 2023; Huda et al, 2018) indicate that students who participate in online learning that focuses on cultural exchange undergo intellectual transformation. In a study (Ahmad & Gul, 2021), participants reported developing a stronger sense of civic leadership and social justice beliefs through online engagements.…”
Section: The Benefits Of Online Discussion Forumsmentioning
confidence: 99%
“…This provided the policy makers and educators with a chance to learn more about the feasibility of online education as well as the measures that could be taken to fill the gaps. One of the main concerns that emerged from the research studies was that the younger age groups need support of parents in most of the educational activities carried out online (Gul et al, 2023). An added burden comes upon parents who had to deal with their daily professional activities as well as supervision of their children's educational activities.…”
Section: Pakistan's Readiness For Online Education Programsmentioning
confidence: 99%
“…The pandemic provided us with a chance to adapt and uncovered many areas of improvement regarding integration of technology in any educational programs. This could lead to innovation in learning like flipped classrooms, blended learning and overall flexible customized approaches to teaching and learning that can be used to achieve literacy rates and student retention ratios in formal education at all levels (Gul et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…School clustering is a new and accepted approach in this regard, which has handled this problem to a great extent. Neighboring schools' cooperation and support in all the required information and resources have enabled the far-sided schools to run normally and properly (Gul, 2023).…”
Section: School Cluster Systemmentioning
confidence: 99%
“…By area, Balochistan is the largest province of Pakistan (Gul et al, 2023). It covers the largest area of Pakistan and is important because of its geographical and statistical location but the resources are not available for the entire population in Balochistan.…”
Section: Introductionmentioning
confidence: 99%